Putting consumers first in food systems analysis: Identifying interventions to improve diets in rural Ghana - Aberman, Noora-Lisa; Gelli, Aulo; Agandin, John; Kufoalor, Doreen S.; Donovan, Jason (Springer, 2022)
A critical, yet underexplored, dimension of food systems is how consumer food preferences and beliefs interact with the food environment. We present a consumer-centered approach to identifying options for improving diets. The Value Chains for Nutrition (VCN) mixed-methods multi-disciplinary analytical approach was applied in rural Ghana. Data from in-depth consumer interviews, structured vendor interviews, and (secondary) household consumption surveys were analyzed to assess consumer diet patterns, related norms and preferences, and supply and demand characteristics of a set of empirically defined high-potential nutritious foods. Mapping results onto a supply–demand typology, we identify promising interventions to support increased availability, access, and affordability of these foods. Consumption data suggested that diets among Ghanaians were deficient in key micronutrients and calories. Fresh nutritious fruits and vegetables tended to be grown for home consumption rather than sale due to transportation challenges and seasonality of demand, especially near rural markets. Seasonal availability (fruits and vegetables) and affordability (animal foods) severely limited consumption of many nutritious foods. A set of supply, demand, and value chain interventions to enhance availability and affordability of nutritious foods are presented. Critical to success is to consider the set of interventions along each value chain required for impact.